Stereotactic brain Interventions: Identifying risks for biopsy failures and hemorrhage - Mohamed Salah Mohamed; Wael Elmesallamy; Ahmed Mohammad Alaa Eldin Shalaby (Interdisciplinary Neurosurgery, 2024)
Background: The advent of computed tomography (CT) and magnetic resonance imaging (MRI) has revolutionized stereotactic brain interventions, which enabled precise targeting of deep brain structures and enhanced patient safety in modern neurosurgery. This study aims to investigate the risk factors associated with biopsy failure and hemorrhage in CT-guided brain stereotactic surgeries. Methods: In the current study, we present a retrospective descriptive analysis of cases that showed biopsy failures and hemorrhage after CT-guided stereotactic brain biopsy surgeries at our department from January 2019 to January 2021. Biopsies were obtained using a Sedan-type needle. Results: Out of the 80 patients who underwent CT-guided stereotactic surgeries, two patients (2.5 %) experienced biopsy failure, necessitating a repeat procedure. There was a notably higher risk of biopsy failure when fewer than four biopsy attempts were made (adjusted odds ratio = 6.4, 95 % CI 1.8 to 16.7). A postprocedural CT scan revealed intracranial hemorrhage in five patients (6.25 %); four of these cases were silent, with no accompanying neurological complications. Four out of the five hemorrhage cases were associated with astrocytoma. Conclusions: Stereotactic surgery provides a precise and minimally invasive approach to target lesions with a relatively low risk of biopsy failures and hemorrhage.